A rare c.183_187dupCTCAC mutation of the acetylcholine receptor CHRNE gene in a South Asian female with congenital myasthenic syndrome: a case report. Issue 1 (December 2016) - Chang, Thashi; Cossins, Judith; Beeson, David
Abstract Background Congenital myasthenic syndromes (CMSs) occur as a result of genetic mutations that cause aberrations in structure and/or function of proteins involved in neuromuscular transmission. Acetylcholine receptor epsilon (ε) subunit (CHRNE ) gene mutations account for about 30–50 % of genetically diagnosed cases. We report a rareCHRNE gene mutation in a South Asian female with CMS. Case presentation A 17-year-old Maldivian female presented with bilateral partial ptosis, fatigable proximal muscle weakness and slurring of speech noted since the age of 2 years. She could not run, had difficulty negotiating stairs and rising from a seated position, and fatigues when speaking at length. Her birth and past medical histories were otherwise unremarkable. There is no parental consanguinity or family history of muscle disorders. On examination, she had a BMI of 18 kg/m2, bilateral fatigable partial ptosis, complete external ophthalmoplegia and fatigable proximal muscle weakness (MRC grade 4/5). Apart from spinal scoliosis the rest of the examination was normal. Haematological and biochemical investigations including serum lactate level and thyroid functions were normal. Acetylcholine receptor antibodies and muscle specific kinase antibodies were not detected in serum. Repetitive nerve stimulation showed marked decrement (>30 %) in nerve-muscle pairs in the face and forearm. Her DNA sequencing revealed a c.183-187dupCTCAC mutation inCHRNE . She remained functionally independent on pyridostigmine treatment. Conclusions This case describes a rare mutation of theCHRNE gene in CMS and highlights the relevance of genetic diagnosis in CMS. It further adds to map the occurrence of such mutations in Asian populations.